The Concept of I'jāz Rasm of the Qur'an According to M. Syamlūl on the Words Hasanāt and Sayyiāt in the Qur'an - Rohmah, Nazilatur; M. Miqdad Al-Ghifari Syatta; Ummuz Zahrah; Nafilah Chaudittisreen; Nazilatur Rohmah (JIA (Jurnal Ilmu Agama), 2024)
The writing of the Qur’an is different from Arabic writing in general even though the pronunciation is the same. The scholars of fiqh, Qur’anic scholars, and theologians agree that the writing of the Qur’an which is different from the writing of Arabic in general is intended to enable the Qur'an to contain al-ahrūf al-sab'ah. It also shows the truth about the existence of miracles in the Qur'an. This miracle became known as i'jāz rasm. The majority of scholars are of the opinion that the writing of the Qur’an is an order of the Prophet Muhammad (tauqīfī), and no one has the right to change it. However, it is still rare for people to discuss the miracle of the Qur’an in terms of writing (rasm). One of the scholars who discussed the i'jāz rasm is M. Syamlūl in his work entitled I'jāz Rasm al-Qur’an wa I'jāz al-Tilāwah. Departing from the above problems, the author tries to examine how the concept of i'jāz rasm according to Syamlūl's view, especially on the words hasanāt and sayyiāt in the Qur’an. The method used in this research is library research with qualitative research. The purpose of this study is to examine the concepts given by Syamlūl about the differences in writing in the Qur’anic rasm. The results of this study reveal that the i'jāz rasm in the Qur'an that focuses on the words hasanāt and sayyiāt is not only related to the differences in writing that may violate Arabic writing in general which shows the uniqueness of the Qur’an alone, but also to the depth of moral messages and implied meanings conveyed through the differences in the writing of the words hasanāt and sayyiāt.